Animal tongues - Cusick, Dawn (Earlylight Books, 2009)
Looks at the varied types of animal tongues and their different uses in adaption to their environment, from the sticky tongue of a chameleon, to the tongue of the lizardfish lined with teeth, to the tongue of the parrot used to make sounds.